Chicken soup for the soul our 101 best stories: dads & daughters; stories about the special relationship between fathers and daughters - Canfield, Jack 1944-; Hansen, Mark Victor; Newmark, Amy (Our 101 best stories, 2008)
A collection of 101 of the best stories about fathers and daughters from Chicken Soup's library. Stories were written by fathers, daughters and granddaughters to provide support, share experiences, enlighten, amuse, and describe their love and admiration for one another.